KORELAT EMPAT LEMBAGA KEBENARAN MANUSIA: Filsafat, Seni, Ilmu, dan Agama - Tri Karyono (Universitas PGRI Adi Buana Surabaya, 2014)
Philosophy is a critical, rational, and radical reflection towards main things in human life. Reflection (Reflekture) is referred to deeply critical self-contemplation. Thinking in a critical manner is to mean to always place everything in consideration and awareness in order to find the answers to the occurring questions. Thus, every philosopher will find their own alternatives with differentlyspeculative answers. When philosophy defined as a science which has the characteristics mentioned above is related to art, another science which has its certain system, even to religion which has absolute truth, it will become something interesting for a study.In this article the author have made some comparison of them and found the tangent point where they complement each otherbecause they, basically, have scope of knowledge in common.